PENGARUH KOMPENSASI, DISIPLIN KERJA DAN MOTIVASI TERHADAP PRODUKTIVITAS KARYAWAN PT. TJIPTA RIMBA DJAJA - Dakhi, Monika Erlina; Tanjung, Yahya (JURNAL WIDYA, 2024)
This research aims to determine the effect of compensation, work discipline and motivation on employee productivity at PT. Tjipta Rimba Djaja. The data collection technique used in this research uses questionnaire data and documentation, the type of research used in this research is quantitative research. The data sources used in this research are primary and secondary data sources. The sample used in this research was 66 respondents. The instrument tests used in this research are validity tests and reliability tests. The data analysis techniques used in this research are descriptive statistical tests, classical assumption tests, multiple linear regression tests and coefficient of determination tests. The results of hypothesis testing in this research show that compensation has a positive and significant effect on employee productivity, then the work discipline variable has an effect on employee productivity and the motivation variable has no effect on employee productivity at PT. Tjipta Rimba Djaja